Model Pencegahan Ulkus Diabetikum Berbasis Six Sigma sebagai Solusi Inovatif dalam Meningkatkan Efisiensi Perawatan Pasien Diabetes Mellitus di RSUD Undata - Agnes Erlita Distriani Patade; Elin Hidayat (Universitas Pahlawan Tuanku Tambusai, 2025)
Diabetic foot ulcer is a serious complication in patients with diabetes mellitus that leads to disability, amputation, and even death, as well as increasing the burden of healthcare costs. At Undata General Hospital, Palu, cases of diabetic foot ulcers have risen significantly, in line with low standards of prevention and care efficiency. This study aimed to develop a Six Sigma-based prevention model for diabetic foot ulcers as an innovative strategy to improve care efficiency. Methods: This research employed an explanatory survey design with a cross-sectional approach. A total sample of 93 inpatient nurses was selected using Slovin’s formula from a population of 122. The research instrument consisted of a structured questionnaire covering individual, organizational, and managerial factors, the implementation of Six Sigma-based prevention, and care efficiency. Data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). Results: Managerial factors significantly influenced Six Sigma-based diabetic foot ulcer prevention (p=0.010) and care efficiency (p=0.011). Individual and organizational factors did not show significant effects on either variable. The implementation of Six Sigma-based prevention was found to have the strongest influence on care efficiency (p=0.000; β=0.568). The R² values indicated that 21.1% of the variability in prevention was explained by individual, organizational, and managerial factors, while 46.9% of care efficiency was explained by Six Sigma implementation.Conclusion: Care efficiency for diabetic patients is more strongly determined by management systems and the implementation of the Six Sigma model rather than individual or organizational factors. The final model highlights that strengthening managerial factors is key to the successful implementation of Six Sigma in reducing diabetic foot ulcer incidence and improving care efficiency.